A Study to Assess the Effectiveness of Planned Teaching Programme on Prevention of Selected Life Style Diseases in Terms of Knowledge and Attitude among Male Adults at Selected PHC of Kheda District - Darshana B. Suthar; Kailash Nagar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background of Study: The World Health Organization (WHO) estimates that life style diseases (with mostly preventable risk factors) are biggest killer across the world. Globally, 60% people die each year from life style diseases. 70% deaths are preventable from all non-communicable diseases by modifying life style. Lifestyle diseases are diseases linked with the way people live their life1. These are non-communicable diseases. This is commonly caused by lack of physical activity, unhealthy eating, alcohol, drugs and smoking2.Objectives: 1. To assess the knowledge and Attitude of male adults before and after administration of a planned teaching programme regarding prevention of selected life style disease. 2. To compare the knowledge and attitude score before and after teaching program. 3. To find out the association of post test attitude score regarding prevention of selected life style diseases with their selected demographic variables.Methodology: The research design adopted for the study was one group pretest posttest, quasi experimental research design3. 50 male adults were selected from selected PHC of kheda district by convenient non probability sampling technique and structured knowledge questionnaire and Likert’s attitude rating scale were prepared to assess the knowledge and the attitude of samples. Reliability of structured knowledge questionnaire and likert’s attitude rating scale were ascertained by using test retest method.Results: The study was conducted at Salun PHC. pre-test knowledge range was 7.27, mean was 14.74, standard deviation was 4.28, median was 14.00 and mode was 12.00 and post-test knowledge range was 21.30, mean was 26.12, standard deviation was 2.20, median was 27 and mode was 27.while pre-test attitude range was 43.55, mean was 50.04, standard deviation was 2.83 and median was 51.and post-test level of attitude, 49(98%) had favourable attitude, 1 (2%) had moderately favourable attitude and none of them had unfavourable. The maximum score was 30, mean was 11.38, standard deviation was 2.47 and paired t-test value was 32.53 that hence there exists a significance effectiveness on level of knowledge before and after administration of planned teaching programme among male adults. The maximum score was 60, mean was 3.40, standard deviation was 3.03, mean percentage was and paired t-test value was 07.93 that hence there exists a significance effectiveness on level of attitude before and after administration of planned teaching programme among male adults